Assessment of People’s Perception on COVID-19 Vaccine Hesitancy in Wukari, Taraba State - Egeonu US; Asindaya GA; Andemam T; James S; Mgbemena N (African Journal of Clinical Medicine and Pharmacy Research, 2026)
COVID-19 vaccine hesitancy remains a major public health challenge in Nigeria despite widespread awareness of the vaccine and its recognized role in preventing infection. This study evaluated the perceived causes of and possible preventive measures against COVID-19 vaccine hesitancy in Wukari Local Government Area of Taraba State, Nigeria. A descriptive research design was adopted, and data were collected through a structured questionnaire administered to 600 respondents selected using a multistage random sampling technique, of which 595 questionnaires were successfully retrieved and analyzed using descriptive statistics and simple percentages. The findings showed that all respondents were aware of the COVID-19 vaccine, yet only 24.4% were willing to be vaccinated. Most respondents were aged 31–60 years (41.2%), with males constituting 65.5% and females 34.5% of the sample. The major perceived causes of vaccine hesitancy were fear of the unknown (26.9%), lack of trust in government (25.2%), and concerns about vaccine side effects (23.5%). The main measures suggested by respondents to reduce hesitancy included making COVID-19 vaccination compulsory (25.2%) and building trust between government and citizens. The study concludes that high awareness alone does not ensure vaccine acceptance, as perceptions shaped by fear, mistrust, and safety concerns remain significant barriers. These findings contribute context-specific evidence for public health planning and imply that extensive multi-target health campaigns and more inclusive engagement with target populations are necessary to address public concerns and improve vaccine acceptance.